Employee Performance Improvement Based on Work Orientation and Career Adaptation Ability Through Job Satisfaction (Study of Fresh Graduate Employees Working in Startup Companies in Jakarta) - Rizky Nabilla Nabil; Wasi Bagasworo (Eastasouth Institute, 2026)
Jakarta, as one of the largest business and economic centers in Indonesia, plays a significant role in national economic growth. There are challenges in meeting the need for competent labor, including utilizing fresh graduates who want to enter the workforce. Fresh graduates face intense competition when searching for jobs, not only among fellow fresh graduates but also with experienced workers. This study focuses on the issues of work orientation and career adaptability and their impact on employee performance through job satisfaction as an intervening variable for fresh graduate employees working at startup companies in Jakarta. The analysis results show that Work Orientation has a positive and significant influence on Employee Performance, Career Adaptability has a positive and significant influence on Employee Performance, Job Satisfaction has no influence and is not significant on Employee Performance, Work Orientation has a positive and significant influence on Employee Performance, Career Adaptability has a positive influence on Employee Performance, Work Orientation has no influence and is not significant on Employee Performance through Job Satisfaction, and Career Adaptability has no influence and is not significant on Employee Performance through Job Satisfaction.